Penerapan Mesin Pemecah Jagung Sederhana Sebagai Solusi Alternatif Pengolahan Pakan Mandiri Bagi Peternak - Sembiring, Jesaya; Saragih, Darwan Edyanto; Sirait, Andre M; Surya, Muhammad (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2024)
Farmers in Karang Sari Village face limitations in animal feed processing due to the continued use of inefficient manual corn cracking methods. This Community Service Project aims to design and implement a simple corn cracking machine based on appropriate technology to improve feed production efficiency. The method used is applied Community Service with a participatory engineering approach, collecting data through observation, interviews, and machine performance testing. The results of the Community Service show that the machine is able to reduce work time by up to 80%, lower operational costs, and improve the quality of corn cracking results. In conclusion, this machine is an effective, affordable, and easy-to-operate alternative solution to support livestock farmers' independence in sustainable feed processing.